Lean six sigma to improve customer service processes: a case study (2024)
The customer service process is crucial to the success of any company, both manufacturing and services, regardless of its size and nature, due to direct contact with the customer before, during, and after the sale of products or services. In the current changing and complex context, a good product or service is not enough; it must be complemented with agile response times, the ability to resolve doubts, concerns, and problems, as well as personalized and friendly attention, which can improve or worsen the customer’s perception of quality. Therefore, companies focus their operations on providing the best customer experience, from design to after-sales service. On the other hand, the COVID-19 pandemic intensified the use of non-face-to-face channels such as websites, chats, and telephone lines. These constitute communication channels with quick and convenient access, allowing customers to inquire about the products. Products or services of a company without having to travel to the offices or units, which is why it is necessary to improve the quality of the response and customer service continually. In this context, the Lean Six Sigma methodology is a valuable tool to improve efficiency and quality in customer service processes. This paper presents the application of Lean Six Sigma methodology to improve the time and quality of attention to a service company’s non-face-to-face channel “telephone line” in a low- and medium-income country. The study problem focuses on long waiting times and the quality of care received. To address this problem, implementing the Lean Six Sigma methodology is proposed by identifying the activities that do not add value to waiting times and that impact the quality of the customer service process. This methodology was carried out through the identification of critical processes, the measurement of waiting times and service quality, the analysis of the data obtained, and the implementation of process improvements. The results show essential improvements in process times, mainly in call waiting times. This systematic, data-driven approach leads to greater operational efficiency and strengthens the relationship between the company and its customers, driving long-term loyalty and retention